2017
DOI: 10.1104/pp.17.01512
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Algal “Chloroplast Lipid Droplet”: The Absence of an Entity That Is Unlikely to Exist

Abstract: The precise localization of the lipid droplets and the metabolic pathways associated with oil production are crucial to the engineering of microalgae for biofuel production. Several studies have reported detecting lipid droplets within the chloroplast of the microalga Chlamydomonas reinhardtii, which accumulates considerable amounts of triacylglycerol and starch within the cell under nitrogen deprivation or high-light stress conditions. Starch undoubtedly accumulates within the chloroplast, but there have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…In wild-type C. reinhardtii, microscopy analyses revealed that LDs formed under nitrogen deprivation appear to be primarily located in the cytosol (Fig. 1B), although in many cases in close association with the chloroplast envelope (18,26,32). These observations are consistent with the assembly of TAGs predominantly in ER membranes.…”
Section: Discussionsupporting
confidence: 73%
“…In wild-type C. reinhardtii, microscopy analyses revealed that LDs formed under nitrogen deprivation appear to be primarily located in the cytosol (Fig. 1B), although in many cases in close association with the chloroplast envelope (18,26,32). These observations are consistent with the assembly of TAGs predominantly in ER membranes.…”
Section: Discussionsupporting
confidence: 73%
“…Fan et al [ 12 ] suggested that C. reinhardtii can utilize DAG from chloroplasts to synthesize TAG, and that the TAG formed in this way is deposited in both the chloroplasts and the cytoplasm LDs. However, it has been recently shown that these chloroplast LDs in C. reinhardtii are actually LDs implanted within the chloroplast invaginations, which are part of the outer membrane of the chloroplast [ 53 ]. Therefore, we inferred that, like C. reinhardtii , diatoms may use a pathway that transports TAG precursors, such as DAG, from the chloroplasts to the LDs through a close association with the outer membrane of the chloroplast.…”
Section: Resultsmentioning
confidence: 99%
“…Among these substances, secondary red carotenoids, such as Ast, rhodoxanthin or eschscholtzxanthin are frequently found in different algae and plant groups under stress conditions (Díaz et al, 1990;Hormaetxe et al, 2004;Lemoine & Schoefs, 2010). In plants and algae, these carotenoids typically accumulate in extraplastidial lipid bodies inside the cytoplasm or to form plastoglobules in plastids (Moriyama et al, 2018). The former are in essence spherical lipid droplets surrounded by a phospholipid monolayer with coating proteins (Pyc et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the lightinduced migration of these globules inside the cell (Figs 13, 15), and the high proportion of free and esterified Ast (80% of total carotenoids) ( Fig. 12) it is very probable that most, if not all, Ast in the cell is contained within these globules, through a process of direct metabolic transfer from the chloroplast to the lipid body (Moriyama et al, 2018). Moreover, the Ast-containing organelles observed in E. sanguinea were structurally very similar to the globules or grains that make up the stigma or eyespots in euglenids (Walne & Arnott, 1967;Kivic & Vesk, 1972).…”
Section: Discussionmentioning
confidence: 99%